Accounting of the German Statutory Pension Scheme: Balance Sheet, Cross‐Sectional Internal Rate of Return and Implicit Tax Rate1. (10th June 2019) - Metzger, Christoph
Abstract: We present a framework for accounting of the German statutory pension scheme and calculate a balance sheet for the period 2005–14. Estimating a funding ratio of about 90 per cent, we present some policy recommendations in order to restore balancing of assets and liabilities. Extending and applying the methodology proposed by Settergren and Mikula (2005), we additionally estimate the aggregate cross‐sectional internal rate of return of the German pension scheme over this period. We are able to show that these internal rates of return are mainly financed by increasing contributions and by increasing unfunded liabilities. Additionally, our analysis reveals that from an expenditure perspective, the major part of the internal rate of return results from changing longevity rather than other changes. We also estimate the implicit tax rates from a cross‐sectional perspective and find that they can mainly be interpreted as an 'implicit wealth tax' on pension wealth. Finally, we analyse the impact of demographic change on the balance sheet employing a population projection. While the pure demographic effect leads to a decreasing funding ratio during population ageing, the automatic balancing mechanisms of the German pension scheme lead to a significant overfunding in the long run from the accounting perspective adopted in the Swedish pension system.